Care to the person in a terminal process in the perception of the nursing students - Rudval Souza da Silva; Claudia Cristina Souza Gribel Oliveira; Álvaro Pereira; Juliana Bezerra do Amaral (Rev Rene)
Objective: to know the experiences of the nursing students regarding the care to the person in a terminal process. Methods: a qualitative study with data collected through semi-structured interviews held with ten nursing students. Results: from the data analysis, two theme categories emerged: Feelings expressed facing the first contact with the patients in a terminal process and care to the patient in a terminal process: dichotomy between theory and practice. When experiencing the care to the person in the dying process, students have shown that the feeling of helplessness was the most striking, among others such as sadness, anguish and insecurity. Conclusion: the practices of care of the nursing team disagree with the academic discussions, denying the discourse that the nurse should be present with the patient, regardless of his clinical condition.